Adoption of Green Fodder Production Practices in Watersheds of Bidar District, Karnataka - Javeed, Md. Arif; Veeranna, KC; Thirumalesh, T; Rathod, Prakashkumar; Gopala, GT; Biradar, Channappagouda (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
An ex-post-facto study was conducted to know the adoption status of green fodder production, reasons for adoption or non-adoption, and constraints faced by using a pretested interview schedule through personal interview method. The study involved 120 respondents of Bidar District , Karnataka, which revealed that the majority of the respondents were non-adopters of fodder production practices followed by adopters (38%). Although this adoption seems to be low, it should be further noted that the status of fodder adoption had improved over the period, which might be due to the implementation of KWDP-Sujala-III project activities in the study area. Further, this study has also focused on the reasons for adoption, non-adoption, and discontinuation of fodder production practices. The study also revealed that farmers faced constraints like scarcity of water, non-availability of inputs, lack of knowledge, etc. in the study area. The study concluded that there is a need to maximize participatory demonstrations and capacity building programs to make the farmers adopt fodder production practices through need-based and demand-driven research and extension approaches for improved dairy production.